2014
DOI: 10.1016/j.schres.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

DNA hypermethylation of serotonin transporter gene promoter in drug naïve patients with schizophrenia

Abstract: A correlation between reduction in 5-HTT expression and DNA hypermethylation of the 5-HTT promoter in drug naïve SCZ patients suggests that an epigenetically defined hypo-activity of 5-HTT may be linked to SCZ pathogenesis. Furthermore, this epigenetic mark in DNA extracted from saliva can be considered as one of the key determinants in a panel of diagnostic and/or therapeutic biomarkers for SCZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 38 publications
3
69
0
Order By: Relevance
“…Furthermore, gene-specific methylation analysis using a larger sample size of 468 individuals, uncovered hypermethylation of glucocorticoid receptor gene (NR3C1) in blood from adolescents affected by traumatic stress or stressful life events in childhood [32]. Although blood or saliva cells are not the most appropriate surrogates for the brain cells affected in psychiatric diseases, recent genomewide studies [4,5] support the previous findings of genespecific promoter DNAM analyses [33][34][35] indicating that some of the epigenetic alterations of brain cells are reflected in peripheral tissues. Additionally, an animal study found that, the blood DNAM changes of FKBP5 involved in the development of major depression following the exposure to traumatic events [36] is representative of the dynamics of glucocorticoid-induced DNAM alterations in the brain [37].…”
Section: Determinants Of Altered Dnam Implicated In Psychopathogenesismentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, gene-specific methylation analysis using a larger sample size of 468 individuals, uncovered hypermethylation of glucocorticoid receptor gene (NR3C1) in blood from adolescents affected by traumatic stress or stressful life events in childhood [32]. Although blood or saliva cells are not the most appropriate surrogates for the brain cells affected in psychiatric diseases, recent genomewide studies [4,5] support the previous findings of genespecific promoter DNAM analyses [33][34][35] indicating that some of the epigenetic alterations of brain cells are reflected in peripheral tissues. Additionally, an animal study found that, the blood DNAM changes of FKBP5 involved in the development of major depression following the exposure to traumatic events [36] is representative of the dynamics of glucocorticoid-induced DNAM alterations in the brain [37].…”
Section: Determinants Of Altered Dnam Implicated In Psychopathogenesismentioning
confidence: 91%
“…The next breakthrough came from the most recent genespecific DNAM analyses which identified promoter DNA hypermethylation of 5-HTT (SLC6A4) in the saliva and postmortem brains of patients with SCZ and hypermethylation of BDNF promoter in blood and reduced expression of A2AR (ADORA2A) associated with DNA hypermethylation in postmortem brains of SCZ patients [33,[48][49]. Confirmation of the initial observations of promising genes in subsefuture science group An update on the epigenetics of psychotic diseases & autism Review quent studies along with corresponding expression is shown in Table 2.…”
Section: Altered Dnam Patterns In Autism and Psychotic Diseasesmentioning
confidence: 99%
“…For example, a recent study (41 cases, 46 controls) across 4 brain regions found many genome regions that displayed differentially methylated DNA [28], while a larger study (689 cases, 645 controls) using blood samples similarly identified many differentially methylated loci [29]. Other studies support the importance of DNA cytosine methylation in schizophrenia [30-32]. Differential DNA methylation studies to date have mapped to major neurotransmitter pathways.…”
Section: Mechanisms Of Epigenetic Regulationmentioning
confidence: 99%
“…Genome-wide DNA methylation profiling Significant differences in DNA methylation at multiple loci [80] 69/63 Brain tissue CHRM1 Hypomethylation [81] 80/71 Peripheral blood BDNF Hypomethylation [82] 35/35 30/30…”
Section: Peripheral Blood Leukocytesmentioning
confidence: 99%
“…So far, few studies have examined the epigenetic effects of antipsychotics directly in humans and results are far from being clear, as detailed in Table 3 [65,78,82,86]. Patients treated with haloperidol showed a level of global methylation almost normal (control-like), as if the drug may partially rescue global hypomethylation reported in schizophrenia [65].…”
Section: Epigenetics and Pharmacology: Novel Effects Of Old Drugs Andmentioning
confidence: 99%